Half adder capabilities of a coupled quantum dot device. (15th April 2016) - Pfeffer, P; Hartmann, F; Neri, I; Schade, A; Emmerling, M; Kamp, M; Gammaitoni, L; Höfling, S; Worschech, L
Abstract: In this paper we demonstrate two realizations of a half adder based on a voltage-rectifying mechanism involving two Coulomb-coupled quantum dots. First, we examine the ranges of operation of the half adder's individual elements, the AND and XOR gates, for a single rectifying device. It allows a switching between the two gates by a control voltage and thus enables a clocked half adder operation. The logic gates are shown to be reliably operative in a broad noise amplitude range with negligible error probabilities. Subsequently, we study the implementation of the half adder in a combined double-device consisting of two individually tunable rectifiers. We show that this double device allows a simultaneous operation of both relevant gates at once. The presented devices draw their power solely from electronic fluctuations and are therefore an advancement in the field of energy efficient and autonomous electronics.